PEMASARAN DAN BUDI DAYA BUNGA ANGGREK DI PAMULANG TANGERANG SELATAN - Jayaun Jayaun; Suhermanto Suhermanto (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2024)
The orchid cultivation and marketing industry in South Tangerang has shown significant development within the horticultural sector. This study explores the general conditions of orchid cultivation, including environmental factors conducive to plant growth and common cultivation techniques. Additionally, the study delves into aspects of orchid marketing, covering strategies employed in marketing local orchid products and addressing challenges in both local and export markets. In the context of technology, the research highlights the role of modern technology in orchid cultivation development, from growth monitoring to harvest processing systems. Key constraints in the industry are also discussed, alongside case studies of successful farmers or companies navigating challenges and leveraging opportunities in the orchid cultivation and marketing industry. The findings aim to provide valuable insights for further development in the orchid industry in South Tangerang, serving as a foundation for sustainable policies and best practices to advance the sector